Rekindling of a Masterful Precedent; Bacteriophage: Reappraisal and Future Pursuits - Abd-Allah, Israa M.; El-Housseiny, Ghadir S.; Yahia, Ibrahim S.; Aboshanab, Khaled M.; Hassouna, Nadia A. (Frontiers in Cellular and Infection Microbiology, 2021)
Antibiotic resistance is exuberantly becoming a deleterious health problem world-wide. Seeking innovative approaches is necessary in order to circumvent such a hazard. An unconventional fill-in to antibiotics is bacteriophage. Bacteriophages are viruses capable of pervading bacterial cells and disrupting their natural activity, ultimately resulting in their defeat. In this article, we will run-through the historical record of bacteriophage and its correlation with bacteria. We will also delineate the potential of bacteriophage as a therapeutic antibacterial agent, its supremacy over antibiotics in multiple aspects and the challenges that could arise on the way to its utilization in reality. Pharmacodynamics, pharmacokinetics and genetic engineering of bacteriophages and its proteins will be briefly discussed as well. In addition, we will highlight some of the in-use applications of bacteriophages, and set an outlook for their future ones. We will also overview some of the miscellaneous abilities of these tiny viruses in several fields other than the clinical one. This is an attempt to encourage tackling a long-forgotten hive. Perhaps, one day, the smallest of the creatures would be of the greatest help.